Focused educational intervention improves intern knowledge of perioperative patient blood management principles. Issue 4 (20th December 2021) - Wyssusek, Kerstin; Taylor, Kate; Concha-Blamey, Sandra
Abstract : A perioperative patient blood management (PBM) educational intervention was implemented for first year postgraduate doctors (interns) at the Royal Brisbane and Women's Hospital (RBWH) following identification of a perioperative PBM training requirement. This quality improvement activity evaluated the effectiveness of this educational intervention in improving intern knowledge of perioperative PBM principles. A 15-question perioperative PBM focused multiple choice questionnaire developed from information attained from comprehensive, evidence and consensus-based guidelines regarding PBM practice was distributed to interns immediately before a compulsory perioperative PBM educational intervention and then again 5 weeks later. The perioperative PBM educational intervention was delivered every 10 weeks (five interventions in total) to a different group of interns each time. Statistical analysis determined significance between mean questionnaire score before and after the intervention. The mean pre-intervention score for correctly answered questions was 7/15 (SD 2.73) and mean post-intervention score was 9/15 (SD 2.99) (p=0.02). Categorisation of questions into core domains of perioperative PBM demonstrated intern scores for correctly answered questions improved in all domains following the educational intervention. Perioperative PBM education delivered through a dedicated intervention aimed to improve knowledge is associated with objective evidence of educational benefits for interns at RBWH. It is an effective strategy to enact PBM governance and bestow clinical guideline knowledge. This is important given the global health sector's challenge to improve patient outcomes despite increasingly restricted funding and pressure on doctors to devote more time to service and less to teaching.